2016
DOI: 10.1371/journal.pone.0166185
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Transcriptomic Alterations Associated with STAT3 Activation in Head and Neck Cancer

Abstract: BackgroundHyperactivation of STAT3 via constitutive phosphorylation of tyrosine 705 (Y705) is common in most human cancers, including head and neck squamous carcinoma (HNSCC). STAT3 is rarely mutated in cancer and the (epi)genetic alterations that lead to STAT3 activation are incompletely understood. Here we used an unbiased approach to identify genomic and epigenomic changes associated with pSTAT3(Y705) expression using data generated by The Cancer Genome Atlas (TCGA).Methods and FindingsMutation, mRNA expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…[ 8 ] STAT3 has been closely linked to various types of cancer, such as pancreatic cancer, stomach cancer, head and neck cancer, and thyroid carcinoma, and contributes to cancer progression by upregulating oncogenes. [ 12 15 ] Some studies have suggested that constitutively active STAT3 binds to one of binding sites of VEGF, which upregulates VEGF expression, promotes angiogenesis, and increases the risk of tumorigenesis. [ 19 ] Varney and Singh [ 7 ] observed that the VEGF-C-VEGFR-3/Flt4 (VEGFR-3) autocrine signaling pathway regulates the survival and proliferation of breast tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8 ] STAT3 has been closely linked to various types of cancer, such as pancreatic cancer, stomach cancer, head and neck cancer, and thyroid carcinoma, and contributes to cancer progression by upregulating oncogenes. [ 12 15 ] Some studies have suggested that constitutively active STAT3 binds to one of binding sites of VEGF, which upregulates VEGF expression, promotes angiogenesis, and increases the risk of tumorigenesis. [ 19 ] Varney and Singh [ 7 ] observed that the VEGF-C-VEGFR-3/Flt4 (VEGFR-3) autocrine signaling pathway regulates the survival and proliferation of breast tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 11 ] Moreover, constitutive expression of signal transducer and activator of transcription 3 (STAT3) is significantly associated with tumor formation, migration, and invasion in various cancers, such as papillary thyroid carcinoma, pancreatic cancer, head and neck cancer, and gastric cancer. [ 12 15 ] However, the mechanisms underlying positive correlation between expression of STAT3 in breast cancer patients and lymph node metastasis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to miR-197, PD-L1 is regulated by other microRNAs, including miR-138-5p, miR-513, miR-570, miR-34a, and miR-200, the functions of which have not yet been elucidated in OSCC [ 14 - 18 ]. Considering previously reported clinically relevant signaling pathways involving CKS1B and STAT3 in OSCC and the known miR-197/CKS1B/STAT3/PD-L1 pathway [ 12 , 13 , 19 - 21 ], we focused on the miR-197/PD-L1 axis and TILs.…”
Section: Introductionmentioning
confidence: 99%
“…Using CasP subtyping, HNSCC patients were stratified into two distinct groups, including (i) patients with mutations in TLR signaling who have better OS and (ii) patients with mutations in T and B cell receptor signaling who have poorer survival (179). Also, another study identified genomic and/or epigenomic changes that lead to STAT3 activation in HNSCCs using data generated by the TCGA and the TCPA programs (233). The authors identified that STAT3 expression is associated with disease stage, nodal status, tumor size, PFS, and OS in early stage oral HNSCCs.…”
Section: Bioinformatics Analysis Of the Cancer Genome Atlas And The Cancer Proteome Atlas Hnscc Datamentioning
confidence: 99%